Bipolar electrode, method of manufacturing the same, bipolar secondary battery comprising the same
Patent Information
- Application Number
- CN202580020864.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-09-08
- Filing Date
- 2025-09-09
- Publication Date
- 2026-10-16
AI Technical Summary
然而,这种配置可能具有这样的缺点:其不仅使双极电极的整个制造过程过于复杂,而且其还使得难以控制负极混合物层的负载量
[0020] The bipolar electrode according to the embodiments of this disclosure replaces the positive electrode mixture layer formed by conventional wet processes and includes a positive electrode mixture film formed by dry processes without a separate solvent.
Smart Images

Figure CN122935820A_ABST
Abstract
Description
Technical Field
[0001] Cross-reference to related applications
[0002] This application claims priority and benefit to Korean Patent Application No. 10-2024-0123554, filed on September 10, 2024; Korean Patent Application No. 10-2024-0173645, filed on November 28, 2024; and Korean Patent Application No. 10-2025-0127214, filed on September 8, 2025, the entire contents of which are incorporated herein by reference.
[0003] This disclosure relates to a bipolar electrode, a method of manufacturing the same, and a bipolar secondary battery including the same, said bipolar electrode exhibiting reduced damage to the negative electrode mixture layer during the rolling process and enabling the formation of a positive and a negative electrode with consistent porosity on both surfaces of a metal current collector. Background Technology
[0004] Recently, as the application of lithium secondary batteries has rapidly expanded beyond supplying power to electronic devices such as electrical equipment, electronic equipment, communication equipment, and computers, to storing and supplying power to large-area devices such as automobiles and energy storage systems, the demand for secondary batteries with high capacity, high output, and high stability is increasing.
[0005] Conventional lithium-ion rechargeable batteries typically have a structure in which multiple cell units are connected in parallel, and each cell unit has a single positive and negative electrode, each coated with an active material of the same polarity on a current collector, and a separator or electrolyte layer between them. In such a conventional battery structure, from the perspective of the current flow path, problems such as increased resistance, reduced power density, and low safety may occur.
[0006] Therefore, there has been a significant increase in interest and research recently regarding bipolar secondary batteries, including bipolar electrodes. Bipolar electrodes have structures in which active materials of different polarities are coated on the two surfaces of the current collector, and bipolar secondary batteries have structures in which a plurality of bipolar electrodes are laminated with spacers or electrolyte layers interposed between them.
[0007] Such bipolar secondary batteries have a structure in which cell units are connected in series, defined by positive and negative electrodes facing each other and a separator or electrolyte layer between them. Therefore, bipolar secondary batteries can shorten the path of current flow, reduce resistance, and increase power density, which simplifies the components and structure used to control the individual cell units within a module or group comprising bipolar secondary batteries.
[0008] However, bipolar electrodes suffer from the disadvantage of difficult electrode formation processes, particularly rolling processes, due to the formation of active material and mixture layers with different properties on the two surfaces of the current collector. As a typical example, lithium transition metal oxides can be used as the positive electrode active material in bipolar electrodes, and graphite-based active materials can be used as the negative electrode active material. However, graphite-based active materials have lower strength and ductility compared to lithium transition metal oxides, and therefore, when the two surfaces of the bipolar electrode are rolled under the same conditions, it may be difficult to achieve the desired porosity or rolling density for the positive electrode mixture layer (during rolling of the negative electrode mixture layer), or damage may occur to the negative electrode mixture layer, especially its edges (during rolling of the positive electrode mixture layer).
[0009] To address these issues, one approach could be to first form and dry the positive electrode mixture layer, then pre-roll the positive electrode mixture layer before forming and drying the negative electrode mixture layer, and finally perform a secondary roll forming on both surfaces after forming and drying the negative electrode mixture layer. However, this configuration may have drawbacks: it not only complicates the entire manufacturing process of the bipolar electrode but also makes it difficult to control the loading of the negative electrode mixture layer. Summary of the Invention
[0010] Technical issues
[0011] Therefore, this disclosure provides a bipolar electrode and a method for manufacturing the same, which simplifies the manufacturing process of the bipolar electrode, particularly the rolling process, while reducing damage to the negative electrode mixture layer during the rolling process and enabling the formation of negative and positive electrodes with consistent porosity.
[0012] Furthermore, this disclosure provides a bipolar electrode assembly and a bipolar secondary cell that include the bipolar electrode and thus exhibit excellent physical and electrochemical properties.
[0013] Technical solution
[0014] According to one aspect of this disclosure, a bipolar electrode is provided, comprising: a metal current collector; a negative electrode mixture layer coated on one surface of the metal current collector and comprising a polymer binder, a conductive material, and a negative electrode active material; and a positive electrode mixture film attached to another surface of the metal current collector and comprising a fibrous polymer binder, a conductive material, and a positive electrode active material.
[0015] In one embodiment of the bipolar electrode, the positive electrode mixture film can be a dry film produced in the absence of solvent, and the negative electrode mixture layer can be a wet mixture layer produced by coating a slurry composition in which a polymer binder, a conductive material and a negative electrode active material are dispersed in an organic solvent onto a surface of a metal current collector, and then drying the slurry composition.
[0016] According to another aspect of this disclosure, a method for manufacturing a bipolar electrode according to one embodiment is provided. The manufacturing method may include the steps of: coating a slurry composition comprising a polymer binder, a conductive material, a negative electrode active material, and an organic solvent onto one surface of a metal current collector, and then drying it to form a negative electrode mixture layer; dry-blending and calendering a fiberizable polymer binder, a conductive material, and a positive electrode active material to form a positive electrode mixture film; attaching the positive electrode mixture film to another surface of the metal current collector; and applying pressure to the negative electrode mixture layer and the positive electrode mixture film to roll them.
[0017] According to another aspect of this disclosure, a bipolar electrode assembly is provided, which is configured such that the bipolar electrodes of one embodiment are alternately laminated by a separator, an electrolyte layer, or a laminate thereof, and the negative electrode mixture layer and the positive electrode mixture film of adjacent bipolar electrodes face each other with a separator, an electrolyte layer, or a laminate thereof inserted between them.
[0018] According to another aspect of this disclosure, a bipolar secondary battery is provided, comprising: a bipolar electrode assembly; an electrode terminal electrically connected to the outermost electrode of the bipolar electrode assembly; and a housing for the bipolar electrode assembly.
[0019] Beneficial effects
[0020] The bipolar electrode according to the embodiments of this disclosure replaces the positive electrode mixture layer formed by conventional wet processes and includes a positive electrode mixture film formed by dry processes without a separate solvent.
[0021] The positive electrode mixture membrane is produced in the form of a self-supporting membrane, for example, by dry mixing components such as positive electrode active materials and then calendering the mixture, and can be pressed independently before being attached to the metal current collector of the bipolar electrode.
[0022] Therefore, in one embodiment of a bipolar electrode including a positive electrode mixture membrane, after the membrane is attached to the current collector, even when rolling is performed by applying equal pressure (e.g., a pressure suitable for the negative electrode mixture layer) to the negative electrode mixture layer and the positive electrode mixture membrane, the desired level of porosity and rolling density can be achieved for both without the risk of damaging the edges of the negative electrode mixture layer.
[0023] Furthermore, the bipolar electrode of one embodiment can be manufactured with the formation process of each electrode mixture layer (mixture film) and the rolling process simplified, and even with the simplified process, it can exhibit excellent physical and electrochemical properties, such as the same porosity between the positive and negative electrodes.
[0024] Therefore, the bipolar electrode of one implementation scheme can greatly facilitate the manufacture of bipolar secondary batteries with excellent physical properties through a simplified process. Attached Figure Description
[0025] Figure 1 This is a schematic cross-sectional view of a bipolar electrode according to one embodiment of the present disclosure.
[0026] Figures 2a to 2e This is a schematic step-by-step diagram illustrating a method for manufacturing a bipolar electrode according to another embodiment of the present disclosure.
[0027] Figure 3 This is a schematic cross-sectional view of a bipolar electrode assembly according to another embodiment of this disclosure. Detailed Implementation
[0028] In the following description and claims, the terms or words used should not be construed as limited to their ordinary or dictionary meanings, and this disclosure should be interpreted as having meanings and concepts consistent with the technical concept of this disclosure, based on the principle that inventors can appropriately define the concepts of terms in order to best describe their own inventions.
[0029] Unless otherwise defined, all terms used herein (including technical and scientific terms) are to be used in the sense that would be normally understood by one of ordinary skill in the art to which this disclosure pertains. Furthermore, unless specifically and explicitly defined, terms as defined in commonly used dictionaries should not be interpreted ideally or excessively.
[0030] The technical terms provided herein are for the purpose of describing particular embodiments only and are not intended to limit this disclosure. Unless the context clearly indicates otherwise, the singular form is intended to include the plural form as well. The terms “comprising” and / or “including” as used herein do not exclude the presence or addition of one or more elements other than those mentioned.
[0031] Throughout this description, when a component “includes” a member, unless otherwise defined, this does not mean that the component does not include other components, but rather that the component may include other components.
[0032] Throughout this description, the term "(positive or negative) mixture membrane" is used to define a membrane produced by a dry process, unlike a "(positive or negative) mixture layer" produced by a wet process. For example, unlike a "(positive or negative) mixture layer" formed by coating a slurry in which active materials, binders, and conductive materials are dispersed in an organic solvent onto a current collector and drying the slurry, a "(positive) mixture membrane" can refer to a membrane formed by mixing active materials, binders (e.g., fibrous binders), and conductive materials in a dry state and calendering the mixture under pressure. This "(positive) mixture membrane" may have different morphology and properties from a "(positive or negative) mixture layer," for example, in terms of the residual solvent, the morphology of the fibrous binder, or the porosity immediately following production.
[0033] The following describes several embodiments of the present disclosure in detail with reference to the accompanying drawings, enabling those skilled in the art to readily implement them. Throughout this specification and the drawings, identical or similar components will be indicated by the same reference numerals.
[0034] like Figure 1 As shown, a bipolar electrode 1 according to one embodiment of the present disclosure may include: a metal current collector 10; a negative electrode mixture layer 20 coated on one surface of the metal current collector 1 and comprising a polymer binder, a conductive material, and a negative electrode active material; and a positive electrode mixture film 30 attached to the other surface of the metal current collector 10 and comprising a fibrous polymer binder, a conductive material, and a positive electrode active material. In the bipolar electrode 1 according to one embodiment, the positive electrode mixture film 30 may be a dry film produced in the absence of a solvent, and the negative electrode mixture layer 20 may be a wet mixture layer produced by coating a slurry composition in which the polymer binder, conductive material, and negative electrode active material are dispersed in an organic solvent onto one surface of the metal current collector 10, and then drying the slurry composition.
[0035] In a more specific instance, the type of metal current collector 10 is not particularly limited; however, in one specific instance, it may be a single-layer metal current collector comprising stainless steel (SUS), or a current collector comprising a metal laminate including an aluminum layer and a copper layer. In a more specific embodiment, when using a metal current collector comprising a metal laminate, the aluminum layer may contact the positive electrode mixture membrane 30, and the copper layer may contact the negative electrode mixture layer 20.
[0036] Furthermore, in metal current collectors comprising metal laminates, a separate underlay or adhesive layer can be added between the aluminum and copper layers to improve their bonding strength. However, from the perspective of energy density and resistivity, it is more suitable for the aluminum and copper layers to be directly attached without adding a separate layer. The aluminum and copper layers can be attached at their contact surfaces by methods such as welding.
[0037] The metal current collector 10, including stainless steel (SUS) or metal laminates, can exhibit electrochemical stability over the entire voltage range in which the bipolar secondary cell operates, and can exhibit appropriate adhesion strength to the positive electrode mixture film 30.
[0038] Furthermore, the thickness of the metal current collector 10 can be, for example, from 3 μm to 200 μm, or from 5 μm to 100 μm. In more specific examples, the thickness of the metal current collector 10, including stainless steel, can suitably be from 5 μm to 100 μm or from 7 μm to 40 μm, and the thickness of the metal current collector 10, including a metal layer composite, can suitably be from 20 μm to 200 μm or from 30 μm to 100 μm. In this case, the thickness of the aluminum layer can be from 10 μm to 100 μm or from 20 μm to 70 μm, and the thickness of the copper layer can be from 1 μm to 100 μm or from 2 μm to 30 μm.
[0039] If the thickness of the metal current collector 10 is too small, it may not be able to properly support the bipolar electrodes, or pinholes may appear between the metal layers. If the thickness of the metal current collector 10 is too large, the overall energy density of the battery may decrease.
[0040] Meanwhile, the positive electrode mixture membrane 30 can be, for example, a dry film produced by mixing positive electrode active material powder comprising lithium transition metal oxide, a fibrous polymer binder, and a conductive material in a dry state, and then calendering the mixture under pressure. This positive electrode mixture membrane 30 can be formed as a self-supporting membrane, wherein the binder is fibrous during processing, while the positive electrode active material and the conductive material are uniformly dispersed on the fibrous binder. For reference, such a dry film form of a positive electrode mixture membrane and a method for producing it are disclosed in U.S. Patent Nos. 8,815,443 and 10,153,096, among others.
[0041] A bipolar electrode 1 according to one embodiment of the present disclosure includes a negative electrode mixture layer 20 produced by a conventional wet process on one surface of a metal current collector 10, and includes a positive electrode mixture film 30 produced by a dry process on the other surface of the metal current collector 10. Since a certain amount of pressure is applied during the calendering process, the positive electrode mixture film 30 itself may exhibit reduced porosity, or it may be produced in the form of a self-supporting film and then separately subjected to preliminary rolling, so as to be able to exhibit porosity reduced to a certain extent.
[0042] Therefore, even if the negative electrode mixture layer 20 and the positive electrode mixture film 30 are rolled by attaching the positive electrode mixture film 30 to the metal current collector 10 and then applying an equivalent pressure sufficient to achieve the target porosity of the negative electrode mixture layer 20, the porosity and rolling density suitable for the positive electrode mixture film 30 can be achieved. Accordingly, the bipolar electrode 1 of one embodiment can achieve desired levels of adhesive strength, porosity and rolling density for the negative electrode mixture layer 20 and the positive electrode mixture film 30, without the risk of damaging the edges of the negative electrode mixture layer 20 due to excessive pressure during the rolling process.
[0043] Meanwhile, in the bipolar electrode 1 of one embodiment, the negative electrode mixture layer 20 may include a polymer binder, a conductive material and a negative electrode active material, and may be a wet mixture layer produced by coating a slurry composition in which the polymer binder, the conductive material and the negative electrode active material are dispersed in an organic solvent onto one surface of the metal current collector, and then drying the slurry composition.
[0044] In this negative electrode mixture layer 20, the negative electrode active material may include: graphite-based active materials, such as non-graphitizable carbon and graphite-based carbon; metal composite oxides, such as Li x Fe₂O₃ (0≤x≤1), Li x WO₂ (0≤x≤1), Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, Group 1, Group 2 and Group 3 elements in the periodic table, halogen; 0<x≤1; 1≤y≤3; 1≤z≤8); lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; silicon-based oxides, such as SiO, SiO / C, SiO x(1<x<2) and SiO₂; metal oxides, such as SnO, SnO₂, PbO, PbO₂, Pb₂O₃, Pb₃O₄, Sb₂O₃, Sb₂O₄, Sb₂O₅, GeO, GeO₂, Bi₂O₃, Bi₂O₄ and Bi₂O₅; conductive polymers, such as polyacetylene; or Li-Co-Ni based materials. Among them, in consideration of factors such as good formation and adhesive strength of the negative electrode mixture layer 20 on the metal current collector 10, it is preferable to use a graphite-based active material as the negative electrode active material.
[0045] Based on the total weight of the negative electrode mixture layer 20, the negative electrode active material may be included in an amount of, for example, 80 wt% to 99 wt% or 85 wt% to 98 wt%.
[0046] In addition, as the polymer binder for the negative electrode mixture layer 20, any polymer binder known to be usable for the negative electrode mixture layer of a lithium secondary battery can be used without any particular limitation. Specific examples of such polymer binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene butadiene rubber, fluororubber, or various copolymers thereof.
[0047] Typically, based on the total weight of the negative electrode mixture layer 20, the polymer binder may be included in an amount of 0.5 wt% to 15 wt%, or 0.7 wt% to 10 wt%.
[0048] The conductive material contained in the negative electrode mixture layer 20 is not particularly limited as long as it has electrical conductivity without causing chemical changes in the battery, and for example, the following can be used: graphite, such as natural graphite or artificial graphite; graphene; activated carbon; activated carbon fiber; carbon black, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black or thermal black; conductive fibers, such as carbon fiber or metal fiber; metal powder, such as fluorinated carbon powder, aluminum powder and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; conductive materials such as polyphenylene derivatives; and the like, however specifically, to ensure uniform mixing and improve electrical conductivity, the conductive material may include at least one selected from activated carbon, graphite, carbon black, graphene, and single-walled or multi-walled carbon nanotubes, and more specifically, it may include carbon black or activated carbon.
[0049] Based on the total weight of the negative electrode mixture layer 20, the conductive material may be included in an amount of 0.1 wt% to 15 wt%, or 0.5 wt% to 10 wt%.
[0050] Considering the total thickness, resistance, and other electrochemical characteristics of the bipolar electrode 1 and the bipolar secondary cell, the negative electrode mixture layer 20 can have a thickness of, for example, 20 μm to 200 μm, 20 μm to 150 μm, or 30 μm to 100 μm and a porosity of 20% to 40%, 22% to 40%, or 25% to 35%. Furthermore, the negative electrode mixture layer 20 can have a porosity of 150 mg / 25 cm² per unit area of the bipolar electrode 1. 2 Up to 400 mg / 25 cm 2 Or 200 mg / 25 cm 2 Up to 400 mg / 25 cm 2 The loading includes negative electrode active material. Therefore, when combined with the positive electrode mixture membrane 30 described below, it can exhibit appropriate capacity and / or output characteristics.
[0051] Meanwhile, in one embodiment of the bipolar electrode 1, the positive electrode mixture membrane 30 comprises a fibrous polymer binder, a conductive material, and a positive electrode active material. In a specific example, the conductive material and the positive electrode active material may, for example, be uniformly dispersed in particulate form on the fibrous polymer binder.
[0052] There are no particular restrictions on the positive electrode active material, as long as it is in the form of lithium transition metal oxide, lithium metal phosphate, or metal oxide. Specific examples of such positive electrode active materials include: layered compounds, such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or compounds substituted with one or more transition metals; such as those of the formula Li 1+x Mn 2-x Lithium manganese oxides of O4 (where x is 0 to 0.33), LiMnO3, LiMn2O3, LiMn2O3 and LiMnO2; lithium copper oxides (Li2CuO2); vanadium oxides, such as LiV3O8, LiFe3O4, V2O5 and Cu2V2O7; and LiNi 1-x M x Ni-site type lithium nickel oxides represented by O2 (where M = Co, Mn, Al, Cu, Fe, Mg, Ca, Zr, Ti, B, P, W, Si, Na, K, Mo, V, Nb, Ru, or Ga, and x = 0.01 to 0.3); LiMn 2-x M xLithium manganese composite oxides represented by O2 (where M = Co, Ni, Fe, Cr, Zn or Ta, and x = 0.01 to 0.1) or Li2Mn3MO8 (where M = Fe, Co, Ni, Cu or Zn); LiMn2O4 in which some Li atoms are replaced by alkaline earth metal ions; lithium metal phosphate LiMPO4 (where M is Fe, Co, Ni or Mn); disulfide compounds; Fe2(MoO4)3; and so on, but not limited to these.
[0053] Considering the physical, electrochemical, and stability characteristics of the bipolar battery 1, lithium metal phosphate LiMPO4 (where M is Fe, Co, Ni, or Mn) is preferred, and more specifically lithium iron phosphate is preferred as the positive electrode active material.
[0054] The positive electrode active material may be included in an amount of, for example, 80% to 99% or 85% to 98% of the total weight of the positive electrode mixture membrane 30.
[0055] Furthermore, the positive electrode mixture membrane 30 can be produced using a fibrous polymer binder for dry processes, and can include a polymer binder in a fibrous form in the final production state. For the purposes of adhesion to the metal current collector 10 and the formation of a well-supported dry membrane, the fibrous polymer binder used herein can be a polyolefin-based polymer bonded with a plurality of fluorine atoms, such as a polyfluoroethylene polymer with multiple fluorine substitutions, like polytetrafluoroethylene (PTFE). The fibrous polymer binder can be included in an amount of at least 50% by weight or more, 60% by weight or more, or 70% by weight or more to 100% by weight of the total polymer binder content of the positive electrode mixture membrane 30.
[0056] In addition to the aforementioned fibrous polymer binder, the positive electrode mixture membrane 30 may also contain other polymer binders, and examples may further include PEO (polyethylene oxide), PVdF (polyvinylidene fluoride), PVdF-HFP (polyvinylidene fluoride-copolymer-hexafluoropropylene), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, or various copolymers thereof.
[0057] Furthermore, based on the total weight of the positive electrode mixture membrane 30, the polymer binder, which includes the fibrous polymer binder as a major component, may be included in an amount of 0.5% to 15% by weight, or 0.7% to 10% by weight.
[0058] Furthermore, the type and content of conductive materials that may be included in the positive electrode mixture film 30 are basically the same as those included in the negative electrode mixture layer 20, and therefore further description thereof will be omitted.
[0059] In some cases, the positive electrode mixture membrane 30 may also contain fillers as components for suppressing electrode expansion. There are no particular limitations on the filler, as long as it is a fibrous material that will not cause chemical changes in the battery. For example, it may be made of olefin-based polymers such as polyethylene or polypropylene, or fibrous materials such as glass fiber or carbon fiber.
[0060] Considering the total thickness, resistance, and other electrochemical characteristics of the bipolar electrode 1 and the bipolar secondary cell, the aforementioned positive electrode mixture film 30 can have a thickness of, for example, 20 μm to 300 μm or 30 μm to 200 μm and a porosity of, for example, 20% to 40% or 22% to 38%. As described above, one embodiment of the bipolar electrode 1 includes a positive electrode mixture film 30 produced by a dry process, and therefore, even when the negative electrode mixture layer 20 and the positive electrode mixture film 30 are rolled under uniform pressure without applying excessive pressure to or damaging the negative electrode mixture layer 20, the required porosity, etc., of the positive electrode mixture film 30 can be easily met.
[0061] In a more specific instance, the required characteristics of the bipolar electrode 1 can vary depending on the type and purpose of the bipolar secondary battery in which the bipolar electrode 1 is applied. For example, when the bipolar electrode 1 of one embodiment is used in a bipolar secondary battery applied as a power source for a hybrid vehicle or plug-in hybrid vehicle, the bipolar secondary battery requires relatively high power output characteristics and low resistance, rather than increased capacity characteristics and energy density.
[0062] For this purpose, based on the single bipolar electrode 1 included in the cell, the bipolar electrode 1 used in such a hybrid vehicle secondary battery or plug-in hybrid vehicle secondary battery needs to exhibit relatively high porosity, low loading of electrode active material (e.g., positive electrode active material), and small thickness. This is because the impregnation characteristics of the electrolyte on the positive electrode mixture film 30 are increased, and therefore, the resistance of each cell and the bipolar electrode 1 can be reduced.
[0063] Examples of such a bipolar electrode 1 may include, for example, a bipolar electrode 1 with a density of 150 mg / 25 cm². 2 Up to 400 mg / 25 cm 2 200 mg / 25 cm 2 Up to 350 mg / 25 cm 2 Or 250 mg / 25 cm2 Up to 300 mg / 25 cm 2 A positive electrode mixture membrane 30 with a small loading of positive electrode active material is provided. Furthermore, such a positive electrode mixture membrane 30 can have a thickness of, for example, 20 μm to 90 μm, 20 μm to 70 μm, or 30 μm to 50 μm, and a relatively large porosity of 30% to 40%, or 32% to 38%. This sufficiently meets the characteristics required for secondary batteries used in hybrid vehicles or plug-in hybrid vehicles.
[0064] Meanwhile, in another example of the bipolar electrode 1 in one embodiment, such a bipolar electrode 1 can be used, for example, in a bipolar secondary battery used as a power source for an electric vehicle. In this case, the bipolar secondary battery needs to have higher capacity characteristics and energy density.
[0065] For this purpose, based on a bipolar electrode 1 included in the cell, the bipolar electrode 1 included in such a secondary battery for electric vehicles needs to exhibit relatively low porosity, for example, a large loading and thickness of positive electrode active material. Thus, the bipolar secondary battery can exhibit higher capacity characteristics and energy density.
[0066] Another example of such a bipolar electrode 1 may include, for example, a bipolar electrode 1 with a density of 500 mg / 25 cm². 2 Up to 900 mg / 25 cm 2 Or 600 mg / 25 cm 2 Up to 800 mg / 25 cm 2 The high-loading cathode mixture membrane 30 contains a cathode active material. Furthermore, this cathode mixture membrane 30 can have a thickness of, for example, 80 μm to 300 μm, 90 μm to 200 μm, 90 μm to 180 μm, or 100 μm to 150 μm, and a relatively small porosity of 20% to 30%, or 22% to 29%. Thus, the characteristics required for secondary batteries in electric vehicles can be appropriately met.
[0067] In the bipolar electrode 10 used in the above applications, the appropriate thickness of the positive electrode mixture film 30 can be determined based on the positive electrode active material loading and porosity of the positive electrode mixture film 30. Furthermore, the thickness range of the negative electrode mixture layer 20 bonded to the positive electrode mixture film 30 can also be determined based on the appropriate N / P ratio, negative electrode active material loading, and porosity of the negative electrode mixture layer 20.
[0068] Meanwhile, the positive electrode mixture membrane 30 can be attached to the metal current collector 10 with an adhesive strength of 5 gf / 20 mm or greater, or 5 gf / 20 mm to 70 gf / 20 mm, or 15 gf / 20 mm to 65 gf / 20 mm, or 20 gf / 20 mm to 60 gf / 20 mm. This adhesive strength can be measured, for example, by using a UTS (Ultimate Tensile Strength) measuring device and performing a peel test on an electrode sample in which the positive electrode mixture membrane 30 is attached to the metal current collector 10.
[0069] By satisfying the aforementioned adhesive strength, the bipolar electrode 1 of one embodiment can exhibit excellent physical and mechanical properties while maintaining excellent electrochemical properties. To satisfy this adhesive strength, a release film suitable for attaching the positive electrode mixture membrane 30 can be used in the following manufacturing method.
[0070] Furthermore, in some cases, an underlayer can be formed between the metal current collector 10 and the positive electrode mixture film 30 and / or the negative electrode mixture layer 20. This underlayer can contain, for example, conductive and adhesive materials, and can further improve the adhesion properties of the positive electrode mixture film 30 and / or the negative electrode mixture layer 20 to the metal current collector 10. In particular, the need to form an underlayer increases when lithium metal phosphates, such as lithium iron phosphate, are used as the positive electrode active material. This is because the particle strength of lithium iron phosphate is relatively low compared to other positive electrode active materials, such as ternary positive electrode active materials containing nickel, cobalt, and manganese. Due to such low particle strength, lithium metal phosphate particles are difficult to physically embed or fix to the surface of the metal current collector, and the need to form an underlayer may increase because the positive electrode mixture film 30 containing it exhibits relatively low adhesive strength.
[0071] Here, a component equivalent to the conductive material contained in the positive electrode mixture membrane 30 can be used as the conductive material. Furthermore, as a binder, for example, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, etc., can be used.
[0072] In this case, based on the total weight of the underlayer, the content of conductive material can be 5% to 50% by weight, or 5% to 30% by weight, or 10% to 30% by weight. If the content of conductive material is too low, the resistance of the bipolar electrode 1 may increase, and if the content of conductive material is too high, the adhesion strength between the positive electrode mixture film 30 and the metal current collector 10 may decrease. Furthermore, the adhesive material can be included in the remaining amount of the underlayer besides the conductive material. The underlayer can be formed to a thickness of, for example, 0.1 μm to 10 μm.
[0073] Meanwhile, according to another embodiment of this disclosure, a method for manufacturing a bipolar electrode of one embodiment is provided. This manufacturing method may include the following steps: coating a slurry composition comprising a polymer binder, a conductive material, a negative electrode active material, and an organic solvent onto one surface of a metal current collector, and then drying it to form a negative electrode mixture layer; dry-blending and calendering a fiberizable polymer binder, a conductive material, and a positive electrode active material to form a positive electrode mixture film; attaching the positive electrode mixture film to another surface of the metal current collector; and applying pressure to the negative electrode mixture layer and the positive electrode mixture film to roll them.
[0074] In manufacturing methods, such as Figure 2a As shown, a slurry composition comprising a polymer binder, a conductive material, a negative electrode active material, and an organic solvent can be coated onto one surface of a metal current collector 10 and then dried to form a negative electrode mixture layer 20. The type of metal current collector 10 has been described above, and the formation process of the negative electrode mixture layer 20 can follow a typical wet negative electrode process; therefore, further description thereof will be omitted.
[0075] Furthermore, in manufacturing methods according to other embodiments, independent of the formation of the negative electrode mixture layer 20, a fiberizable polymer binder, a conductive material, and a positive electrode active material can be dry-blended and calendered to produce a positive electrode mixture membrane 30 in the form of a self-supporting membrane. The production process of such a positive electrode mixture membrane 30 can follow a general dry electrode membrane formation process known, for example, in U.S. Patent Nos. 8,815,443 and 10,153,096.
[0076] As an example, the positive electrode mixture membrane 30 can be produced by: dry mixing positive electrode active material particles, a fiberizable polymer binder, and conductive material particles; applying shear force to the dry mixture to fiberize the polymer binder; and then calendering the resulting material into a membrane.
[0077] Because a certain amount of pressure is applied during the production process of the positive electrode mixture membrane 30, the positive electrode mixture membrane 30 can be produced with reduced porosity and increased density compared to a positive electrode mixture layer produced by a conventional wet process. Therefore, even when the positive electrode mixture membrane 30 is attached to the metal current collector 10 and then rolled under relatively low pressure, a suitable porosity for the positive electrode mixture membrane 30 can be easily achieved. Therefore, even when the negative electrode mixture layer 20 and the positive electrode mixture membrane 30 are rolled under consistent pressure, a suitable porosity for both the negative electrode mixture layer 20 and the positive electrode mixture membrane 30 can be achieved without damaging the negative electrode mixture layer 20.
[0078] In some cases, a pre-rolling step of the positive electrode mixture membrane 30 may be performed before attaching it to the metal current collector 10, thereby helping to achieve porosity due to the rolling process after attachment to the metal current collector 10.
[0079] Furthermore, after the positive electrode mixture membrane 30 is produced, in order to facilitate attachment to the metal current collector 10, a polyester-based release film 31 can be attached to one surface of the positive electrode mixture membrane 30, such as... Figure 2b As shown, the attachment process can be carried out by laminating the positive electrode mixture film 30 and the polyester-based release film 31 while passing them between opposing pressure rollers 40.
[0080] Since the positive electrode mixture film 30 itself has limitations in adhering to the metal current collector 10, in the presence of the polyester-based release film 31, the positive electrode mixture film 30 adheres to the surface of the metal current collector 10 with high adhesive strength, and subsequently, the polyester-based release film 31 can be removed.
[0081] In this context, to facilitate adhesion to the positive electrode mixture membrane 30 and subsequently make it easy to remove, the polyester-based release film 31 can be a membrane comprising a polymer membrane based on polyalkylene terephthalate bonded with fluorinated functional groups or modified with acrylic functional groups. When a relatively easily removable polymer membrane based on polyalkylene terephthalate modified with acrylic functional groups is used as the polyester-based release film 31, it allows the positive electrode mixture membrane 30 to adhere to the metal current collector 10 while maintaining excellent adhesive strength. In contrast, when different types of release films are used, the adhesive strength of the positive electrode mixture membrane 30 to the metal current collector 10 may weaken during the removal of the polyester-based release film 31, which may lead to deterioration of the physical and mechanical properties of the bipolar electrode 1.
[0082] Simultaneously, after the positive electrode mixture film 30 is formed into a self-supporting film to which a polyester-based release film 31 is attached, it can be stamped into a size corresponding to the negative electrode mixture layer 20, such as... Figure 2c As shown. During this stamping process, a stamping device 50, such as a die-cutting device, can be used.
[0083] Next, as Figure 2d As shown, a positive electrode mixture film 30 with a polyester-based release film 31 attached thereto is attached to another surface of a metal current collector 10 on one surface where a negative electrode mixture layer 20 is formed. Due to the presence of the polyester-based release film 31, the positive electrode mixture film 30 can be attached to the metal current collector 10 with higher adhesive strength.
[0084] Next, as Figure 2e As shown, the polyester-based release film 31 is removed, and pressure can be applied to the negative electrode mixture layer 20 and the positive electrode mixture film 30 for roll pressing. At this time, the positive electrode mixture film 30 is placed in a state where it has already had reduced porosity due to the application of a certain degree of pressure in previous film processing steps, pre-roll pressing steps, release film attachment steps, etc. Therefore, in this roll pressing step, the bipolar electrode can be rolled between the roll pressing rollers 60 under relatively low pressure to achieve the desired porosity of the negative electrode mixture layer 20. In a more specific example, the same pressure, such as 0.5 t / cm to 3.5 t / cm or 1.0 t / cm to 3.0 t / cm, can be applied to the negative electrode mixture layer 20 and the positive electrode mixture film 30 during the roll pressing step, and optimized porosity of the negative and positive electrodes can be easily achieved in such a single roll pressing process.
[0085] On the other hand, according to another embodiment of this disclosure, a bipolar electrode assembly including the aforementioned bipolar electrodes and a bipolar secondary battery are provided. For example... Figure 3 As shown, in the structure of the bipolar electrode assembly, a plurality of bipolar electrodes, including a negative electrode mixture layer 20, a metal current collector 10 and a positive electrode mixture film 30, are stacked alternately via a separator, an electrolyte layer, or a laminate thereof 70, and the negative electrode mixture layer 20 and the positive electrode mixture film 30 of adjacent bipolar electrodes face each other with a separator, an electrolyte layer, or a laminate thereof 70 inserted between them.
[0086] In such an electrode assembly, the positive electrode mixture film 30 and the negative electrode mixture layer 20 facing each other, with a separator, an electrolyte layer, or a laminate 70 therebetween, can be defined as a single cell 100. Figure 3 (The dotted line portion).
[0087] In this configuration, the electrode assembly may consist only of a porous polyolefin-based separator, but it may also include a gel electrolyte layer independent of the separator, or a gel electrolyte-separator layer 70 in which the separator is impregnated with a gel electrolyte. Furthermore, in another specific example, the electrode assembly may consist only of a solid electrolyte layer. This effectively prevents electrolyte leakage from the bipolar secondary battery while simplifying the sealing structure of the bipolar secondary battery.
[0088] In a more specific example, the electrolyte layer comprising a gel electrolyte may contain, for example, a polyurethane- or polyacrylic acid-based crosslinked polymer, a lithium salt, and a non-aqueous organic solvent, and may be in the form in which the lithium salt and non-aqueous organic solvent are dispersed or encapsulated within the crosslinked polymer. However, the types of crosslinked polymers, lithium salts, and organic solvents that may be contained in the gel electrolyte will be apparent to those skilled in the art, and therefore further description thereof will be omitted.
[0089] In another specific example, the solid electrolyte layer may contain any solid electrolyte, for example, selected from at least one of the following: polymer-based solid electrolytes, oxide-based solid electrolytes, sulfide-based solid electrolytes, and halide solid electrolytes. However, the composition of such a solid electrolyte layer may follow that of conventional solid electrolyte layers, and further description thereof will be omitted.
[0090] Meanwhile, in the bipolar electrode assembly, the electrode terminals electrically connected to the current collectors 10a and 10b on both sides of the cell 100 in the lamination direction can be directly connected or indirectly connected via a separate current collector. Furthermore, the bipolar electrode assembly can be housed in a separate housing, and the electrode terminals can be connected to the outside of the housing to form a bipolar secondary battery.
[0091] The above implementation scheme will be described in more detail below with reference to specific embodiments.
[0092] Example 1: Fabrication of a bipolar electrode
[0093] 96 g of LiFePO4 as the positive electrode active material, 0.5 g of carbon black as the conductive material, and 3.5 g of polytetrafluoroethylene (PTFE) as the binder were placed in a mixer and dry-mixed at 10,000 rpm for 1 minute to prepare a mixture. The temperature of the kneader was stabilized at 150°C, and the mixture was placed in the kneader and then run at 50 rpm for 5 minutes under a pressure of 1.1 atmospheres to obtain a mixture block.
[0094] The resulting mixture was placed in a blender and pulverized at 10,000 rpm for 40 seconds, then passed through a sieve with a 1 mm aperture to obtain electrode powder. The prepared electrode powder was then subjected to several passes through a laboratory calender (roller diameter: 88 mm, roll temperature: 100 °C) to produce an electrode powder with a concentration of 700 mg / 25 cm⁻¹. 2 A positive electrode mixture membrane in the form of a self-supporting membrane with a positive electrode active material loading per unit area and a thickness of 100 μm.
[0095] The positive electrode mixture membrane is attached to an acrylic-modified PET release film (product name: acrylic release film, thickness: 25 μm to 100 μm).
[0096] On the other hand, 96 g of graphite as the negative electrode active material, 1.0 g of Super C-65 as the conductive material, and 3.0 g of SBR binder and thickener were mixed in an organic solvent to prepare a slurry. The slurry was coated on one surface of a stainless steel foil (8 μm), dried, and rolled to form a slurry with a thickness of 300 mg / 25 cm⁻¹. 2 The electrode layer loading and the negative electrode mixture layer with a thickness of 100 μm.
[0097] The positive electrode mixture film is then attached to another surface of the stainless steel foil on which the negative electrode mixture layer has not been formed, and the acrylic-modified PET release film is removed.
[0098] Next, the negative electrode mixture layer and the positive electrode mixture film are rolled using a roller press while applying a pressure of 1 ton / cm to 3 ton / cm, thereby manufacturing the bipolar electrode of Example 1.
[0099] Example 2: Fabrication of Bipolar Electrodes
[0100] The bipolar electrode of Example 2 was manufactured in the same manner as in Example 1, except that the positive electrode mixture film was attached to a fluorine-substituted PET release film (product name: fluorine-based release film, thickness: 25 μm to 150 μm).
[0101] Example 3: Fabrication of Bipolar Electrodes
[0102] The bipolar electrode of Example 3 was manufactured in the same manner as in Example 1, except that a current collector comprising an Al / Cu metal laminate (Al thickness: 30 μm to 45 μm and Cu thickness: 3 μm to 10 μm) was used instead of a stainless steel foil (8 μm).
[0103] Comparative Example 1: Fabrication of Bipolar Electrodes
[0104] 96 g of LiFePO4 was used as the positive electrode active material, 0.5 g of carbon black as the conductive material, and 3.5 g of polyvinylidene fluoride (PvDF) as the binder. In these components, the conductive material and binder were pre-injected into an organic solvent and mixed to prepare a pre-dispersion solution. Then, the positive electrode active material was divided into equal portions, added twice, and further mixed to prepare a slurry. This slurry was coated onto one surface of a stainless steel foil (8 μm) and dried to form a slurry with a density of 700 mg / 25 cm⁻¹. 2 The positive electrode mixture layer has a positive active material loading per unit area and a thickness of 100 μm.
[0105] On the other hand, 96 g of graphite as the negative electrode active material, 1.0 g of Super C-65 as the conductive material, and 3.0 g of SBR binder and thickener were mixed in an organic solvent to prepare a slurry. This slurry was coated onto another surface of a stainless steel foil (8 μm) and dried to form a slurry with a thickness of 300 mg / 25 cm⁻¹. 2 The negative electrode mixture layer has a negative electrode active material loading per unit area and a thickness of 100 μm.
[0106] Next, the negative electrode mixture layer and the positive electrode mixture layer were rolled under the same conditions as in Example 1, thereby producing the bipolar electrode of Comparative Example 1.
[0107] Comparative Example 2: Fabrication of Bipolar Electrodes
[0108] A positive electrode mixture membrane with an acrylic-modified PET release film (product name: acrylic release film, thickness: 25 μm to 100 μm) was produced in the same manner as in Example 1.
[0109] 96 g of graphite as the negative electrode active material, 1.0 g of Super C-65 as the conductive material, and 3.5 g of polytetrafluoroethylene (PTFE) as the binder were placed in a blender and mixed at 10,000 rpm for 1 minute to prepare a mixture. The temperature of the kneader was stabilized at 150°C, and the mixture was placed in the kneader and then run at 50 rpm for 5 minutes under a pressure of 1.1 atmospheres to produce a mixture block.
[0110] The resulting mixture was placed in a blender and pulverized at 10,000 rpm for 40 seconds, then sieved through a 1 mm sieve to produce electrode powder. The resulting electrode powder was then subjected to several passes through a laboratory calender (roll diameter: 88 mm, roll temperature: 100°C) to produce an electrode powder with a concentration of 300 mg / 25 cm⁻¹. 2A negative electrode mixture membrane in the form of a self-supporting membrane with a negative electrode active material loading per unit area and a thickness of 100 μm.
[0111] The positive electrode mixture film and the negative electrode mixture film were each attached to the opposite surface of a stainless steel foil (8 μm), and then the release film was removed and rolled under the same conditions as in Example 1 to manufacture the bipolar electrode of Comparative Example 2.
[0112] Example 4: Fabrication of Bipolar Electrodes
[0113] The positive electrode mixture membrane was produced in the same manner as in Example 1, except that it had a concentration of 300 mg / 25 cm⁻¹. 2 It is produced in the form of a self-supporting membrane with a positive electrode active material loading per unit area and a thickness of 50 μm.
[0114] On the other hand, the negative electrode mixture layer was produced in the same manner as in Example 1, except that it had a concentration of 250 mg / 25 cm⁻¹. 2 The negative electrode mixture layer has a negative electrode active material loading per unit area and a thickness of 35 μm.
[0115] Subsequently, the process was carried out in the same manner as in Example 1 to manufacture the bipolar electrode of Example 4.
[0116] Comparative Example 3: Fabrication of Bipolar Electrodes
[0117] The cathode mixture layer was prepared in the same manner as in Comparative Example 1, except that a layer with a concentration of 300 mg / 25 cm⁻¹ was produced. 2 The positive electrode mixture layer has a positive active material loading per unit area and a thickness of 50 μm.
[0118] On the other hand, the negative electrode mixture layer was produced in the same manner as in Comparative Example 1, except that it had a concentration of 250 mg / 25 cm⁻¹. 2 The negative electrode mixture layer has a negative electrode active material loading per unit area and a thickness of 35 μm.
[0119] Subsequently, the process was carried out in the same manner as in Comparative Example 1 to manufacture the bipolar electrode of Comparative Example 3.
[0120] <Experimental Example>
[0121] For the electrodes manufactured in each of Examples 1 to 4 and Comparative Examples 1 to 3, the porosity and adhesion strength of the positive electrode mixture film (positive electrode mixture layer) and the negative electrode mixture layer (negative electrode mixture film) were evaluated by the following method, and the results are shown in Table 1 below.
[0122] - Electrode Adhesion Strength: After cutting the electrode into 2 cm × 10 cm dimensions, double-sided tape was attached to a glass slide, and the surface of the electrode to be measured was adhered to the glass slide using the same tape. The glass slide was then placed in a UTM apparatus, and the electrode layer was peeled off at a 90-degree angle at a speed of 2 m / min to measure the adhesion strength.
[0123] -Porosity:
[0124] To calculate the porosity of an electrode (positive or negative) mixture layer or film, firstly, the loading of each electrode mixture layer or film is divided by its thickness to calculate the electrode density. Then, the porosity is calculated from the electrode density and the true density of the electrode active material according to the following Equation 1:
[0125] [Equation 1]
[0126] P=(1-D) / T×100
[0127] In Equation 1, P represents the porosity of the electrode mixture layer (or mixture film), D represents the electrode density, and T represents the true density of the electrode active material excluding the current collector. In this case, the true density refers to the inherent density of the electrode active material without voids.
[0128] -resistance:
[0129] The resistance of each electrode was measured using an MP (Multi-probe) tester. More specifically, the bipolar electrodes, which were ultimately manufactured through processes such as rolling and drying, were stamped into 5×5 cm shapes. 2 The dimensions of the electrodes were placed in a resistance measuring device, and then the electrode resistance was measured. With a current of 100 μA applied to the positive electrode mixture film (positive electrode mixture layer) and a current of 10 mA applied to the negative electrode mixture layer, the voltage was set to 0.5 V to measure each resistance. The measured resistance values were calculated as relative ratios to the measurements of Example 4, which were set to 100%. These values are shown in Table 1 below.
[0130] [Table 1]
[0131]
[0132] Referring to Table 1, it was determined that in the case of the bipolar electrodes of Examples 1 and 4, the positive electrode mixture film and the negative electrode mixture layer were attached to the metal current collector with excellent adhesive strength, and both sides exhibited good and consistent porosity.
[0133] It was determined that in the case of the bipolar electrodes of Comparative Example 1 and Comparative Example 3, since the positive electrode mixture layer and the negative electrode mixture layer that had undergone the wet process were subjected to the same rolling process, the positive electrode mixture layer was not rolled properly, and the adhesion strength of the positive electrode mixture layer was relatively reduced.
[0134] It was determined that in the case of the bipolar electrode in Comparative Example 2, the negative electrode mixture film was also produced by a dry process, but in this case, the resistance of the bipolar electrode increased compared to Examples 1 to 4.
[0135] On the other hand, Examples 1 to 3 were determined to include those with 600 mg / 25 cm 2 Up to 800 mg / 25 cm 2 The bipolar electrode with a positive electrode active material loading per unit area and a positive electrode mixture film thickness of 90 μm to 130 μm has high capacity characteristics suitable for secondary batteries for electric vehicles.
[0136] Furthermore, it was determined that Example 4 included a concentration of 150 mg / 25 cm⁻¹ 2 Up to 400 mg / 25 cm 2 The bipolar electrode of the positive electrode mixture film with a positive active material loading per unit area and a thickness of 30 μm to 50 μm exhibits low resistance and high output characteristics suitable for secondary batteries for hybrid vehicles, and has superior characteristics compared with similar Comparative Example 3.
[0137] Preparation example: Fabrication of bipolar secondary cells
[0138] Using the bipolar electrodes of the above embodiments or comparative examples, a bipolar secondary battery was manufactured by the following method.
[0139] 100 parts by weight of a solvent containing ethylene carbonate and γ-butyrolactone in a weight ratio of 2:8 were mixed with 3 parts by weight of ethylene carbonate and 0.5 parts by weight of ethyl sulfate. 1 M LiPF6 was added to this non-aqueous organic solvent to prepare an electrolyte. 5 parts by weight of trimethylolpropane ethoxylated triacrylate were mixed with 100 parts by weight of the electrolyte to prepare a composition for forming a gel electrolyte.
[0140] Then, 0.2 g of the gel electrolyte composition was dropped onto and coated onto the negative electrode mixture layer of the bipolar electrode, and the coated surface was rolled to impregnate the composition for forming the gel electrolyte into the negative electrode mixture layer. Then, a strength of 600 W / cm was applied. 2 The coated surface is irradiated with UV light for 5 seconds to form a gel electrolyte layer.
[0141] Five bipolar electrodes, in which a gel electrolyte layer is formed on the negative electrode mixture layer, are stacked together to manufacture a bipolar secondary battery.
[0142] Test Example: Evaluation of the capacity and / or output characteristics of bipolar secondary batteries
[0143] The capacity and output characteristics of the bipolar cells fabricated in the preparation examples were evaluated separately. These capacity and output characteristics were evaluated based on a voltage range of 2.5 V to 3.6 V for each individual cell and a total voltage range of 12.5 V to 18 V for the entire bipolar cell in which five stacks are laminated.
[0144] The results of such capacity characteristic assessments were calculated as a percentage relative to the measurements of Example 4, which were set to 100%. The results of the output characteristic assessments were calculated as a percentage relative to the measurements of Example 1, which were set to 100%. These capacity and output characteristic assessment results are shown in Table 1 above.
Claims
1. A bipolar electrode, comprising: Metal current collector; A negative electrode mixture layer, said negative electrode mixture layer being coated on one surface of the metal current collector, and comprising a polymer binder, a conductive material, and a negative electrode active material; and A positive electrode mixture membrane is attached to another surface of the metal current collector and comprises a fibrous polymer binder, a conductive material, and a positive electrode active material.
2. The bipolar electrode according to claim 1, wherein the metal current collector comprises stainless steel (SUS) or a metal laminate comprising an aluminum layer and a copper layer.
3. The bipolar electrode according to claim 1, wherein the positive electrode mixture film is a dry film produced in the absence of solvent, and The negative electrode mixture layer is a wet mixture layer produced by coating a slurry composition in which the polymer binder, the conductive material and the negative electrode active material are dispersed in an organic solvent onto a surface of the metal current collector, and then drying the slurry composition.
4. The bipolar electrode of claim 1, wherein the fibrous polymer binder comprises a polyolefin-based polymer bonded with a plurality of fluorine atoms.
5. The bipolar electrode according to claim 1, wherein the negative electrode active material comprises a graphite-based active material, and the positive electrode active material comprises lithium iron phosphate.
6. The bipolar electrode of claim 1, wherein the positive electrode mixture film is attached to the metal current collector with an adhesive strength of 5 gf / 20 mm or greater.
7. The bipolar electrode according to claim 1, wherein the porosity of the negative electrode mixture layer and the positive electrode mixture film is 20% to 40%.
8. The bipolar electrode of claim 1, wherein the positive electrode mixture film is at a concentration of 150 mg / 25 cm² per unit area of the bipolar electrode. 2 Up to 400 mg / 25 cm 2 The loading includes the positive electrode active material.
9. The bipolar electrode according to claim 8, wherein the porosity of the positive electrode mixture film is 30% to 40%.
10. The bipolar electrode according to claim 8, wherein the bipolar electrode is used in a secondary battery for a hybrid vehicle or a secondary battery for a plug-in hybrid vehicle.
11. The bipolar electrode of claim 1, wherein the positive electrode mixture film has a concentration of 500 mg / 25 cm² per unit area of the bipolar electrode. 2 Up to 900 mg / 25 cm 2 The loading includes the positive electrode active material.
12. The bipolar electrode according to claim 11, wherein the porosity of the positive electrode mixture film is 20% to 30%.
13. The bipolar electrode according to claim 11, wherein the bipolar electrode is used in a secondary battery for electric vehicles.
14. The bipolar electrode according to claim 1, further comprising an underlayer formed between the metal current collector and the positive electrode mixture film or between the metal current collector and the negative electrode mixture layer, and comprising a conductive material and a binder material.
15. A method for manufacturing a bipolar electrode, the method comprising the following steps: A slurry composition comprising a polymer binder, a conductive material, a negative electrode active material, and an organic solvent is coated onto a surface of a metal current collector and then dried to form a negative electrode mixture layer. A fiberizable polymer binder, conductive material and positive electrode active material are dry-mixed and calendered to form a positive electrode mixture film; Attach the positive electrode mixture film to another surface of the metal current collector; and Pressure is applied to the negative electrode mixture layer and the positive electrode mixture membrane to roll them.
16. The method of manufacturing a bipolar electrode according to claim 15, further comprising, prior to the attachment step, stamping the positive electrode mixture film to a size corresponding to the negative electrode mixture layer.
17. The method of manufacturing a bipolar electrode according to claim 9, wherein the positive electrode mixture film is formed in the form of a self-supporting film to which a polyester-based release film is attached.
18. The method of manufacturing a bipolar electrode according to claim 17, wherein the polyester-based release film comprises a polymer film based on polyalkylene terephthalate modified with fluorinated or acrylic functional groups.
19. The method of manufacturing a bipolar electrode according to claim 17, further comprising removing the polyester-based release film after attaching the positive electrode mixture film.
20. The method of manufacturing a bipolar electrode according to claim 15, further comprising pre-rolling the positive electrode mixture film prior to the attachment step.
21. The method of manufacturing a bipolar electrode according to claim 15, wherein in the rolling step, the same pressure is applied to the negative electrode mixture layer and the positive electrode mixture film.
22. The method of manufacturing a bipolar electrode according to claim 21, wherein in the rolling step, a pressure of 0.5 tons / cm to 3.5 tons / cm is applied.
23. A bipolar electrode assembly configured such that the bipolar electrodes according to any one of claims 1 to 14 are alternately laminated via a separator, an electrolyte layer, or a laminate thereof, and The negative electrode mixture layer and the positive electrode mixture membrane of adjacent bipolar electrodes face each other when the separator, the electrolyte layer, or a composite thereof is inserted between them.
24. The bipolar electrode assembly of claim 23, wherein the electrolyte layer comprises a gel electrolyte comprising a polyurethane- or polyacrylic acid-based crosslinked polymer, a lithium salt, and a non-aqueous organic solvent.
25. The bipolar electrode assembly of claim 23, wherein the electrolyte layer is a solid electrolyte layer, the solid electrolyte layer comprising at least one selected from: polymer-based solid electrolytes, oxide-based solid electrolytes, sulfide-based solid electrolytes, and halide solid electrolytes.
26. A bipolar secondary battery, comprising: The bipolar electrode assembly according to claim 23; The electrode terminals are electrically connected to the outermost electrode of the bipolar electrode assembly; and A housing for the bipolar electrode assembly.
Citation Information
Patent Citations
Curtain height adjustment bracket
KR1020240123554A
Light emitting device, fused polycyclic compound for the light emitting device, and display apparatus including the light emitting device
KR1020240173645A
Electric wires that change color with electricity
KR1020250127214A
Formulations for and methods of fabricating energy storage device electrodes
US10153096B2
Dry-particle based adhesive and dry film and methods of making same
US8815443B2